Pre-operative smoking history increases risk of infection in deep brain stimulation surgery. (November 2019) - Farrokhi, Farrokh R.; Marsans, Maria T.; Sikora, Matt; Monsell, Sarah E.; Wright, Anna K.; Palmer, Meghan; Hoefer, Aiden; McLeod, Pam; Mark, Jamie; Carlson, Jonathan
Highlights: Multisite analysis of DBS surgeries performed over a ten-year period. Statistically significant link between smoking history and post-operative infection. Strong trend towards pre-operative hypertension and intracerebral hemorrhage. Abstract: Although general risk of deep brain stimulation (DBS) therapy has been previously described, application of risk prediction at the individual patient level is still largely at the discretion of a treating physician or a multidisciplinary team. To explore associations between potentially modifiable patient characteristics and common adverse events following DBS surgery, we retrospectively reviewed consecutive adult patients who had undergone new DBS electrode placement surgeries at two high-volume tertiary referral centers between October 1997 and May 2018. Among 501 patients included in the analysis (mean age (SD), 64.6 (10.4) years), 165 (32.9%) were female, 67 (13.4%) had diabetes, 231 (46.1%) had hypertension, 25 (5.0%) were smokers, 27 (5.4%) developed an infection, 15 (3.0%) had intracranial or intraventricular hemorrhage, and 53 (10.6%) had an unplanned return to the operating room. Patients who developed a surgical site infection were more likely to report history of smoking before DBS surgery (16% vs 5%, p = 0.04). There was a trend for patients with hypertension to be at risk for intracranial hemorrhage ( p = 0.11). In conclusion, this multicenter study demonstrated an association between preoperative smoking and increased risk of infection following new DBS implantation surgery. Counseling about this risk should be considered in preoperative evaluation of patients who are considering undergoing a DBS procedure.